1986
DOI: 10.1007/bf00435648
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the influence of fibrin adhesive, factor XIII, and calcitonin on the incorporation and remodeling of autologous bone grafts

Abstract: In an experimental study on sheep the effects of fibrin adhesive system (FAS), plasma factor XIII (FXIII), and calcitonin on autologous cancellous bone grafts were studied. Drill holes in the tibia were filled with transplant bone, either untreated or locally treated with fibrin adhesive, with or without plasma factor XIII. We used 24 sheep, divided into three groups. Plasma factor XIII and calcitonin were administered parenterally; the third group received no treatment. For evaluation we carried out quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Gerngross et al noted a negative impact on bone remodeling in the cortical tibia of a sheep model upon the addition of a fibrin sealant on autologous cancellous bone grafts. 20 Lappalainen et al 21 also observed a similar result upon the association of a fibrin glue with autologous particulate bone in rabbit critical-sized calvarial defects. The negative effect was explained by the potential role of fibrin in limiting the ingrowth of vessels into the grafted bone or its role as a void filler which prevents the formation of the natural fibrin.…”
Section: Injectable Fibrin-based Tissue Engineeringmentioning
confidence: 70%
See 2 more Smart Citations
“…Gerngross et al noted a negative impact on bone remodeling in the cortical tibia of a sheep model upon the addition of a fibrin sealant on autologous cancellous bone grafts. 20 Lappalainen et al 21 also observed a similar result upon the association of a fibrin glue with autologous particulate bone in rabbit critical-sized calvarial defects. The negative effect was explained by the potential role of fibrin in limiting the ingrowth of vessels into the grafted bone or its role as a void filler which prevents the formation of the natural fibrin.…”
Section: Injectable Fibrin-based Tissue Engineeringmentioning
confidence: 70%
“…18,19 Variations in experimental design, implantation site, and animal models as well as fibrinogen and thrombin concentrations are other parameters that make direct comparison of the research findings difficult. Moreover, to achieve the desired biological and/or physical properties for bone tissue engineering applications, fibrin must be reinforced, and there is a board range of nano-and other materials such as autogenous bone grafts, 20,21 allogenic bone grafts, 22,23 xenogeneic bone grafts, 24 metals, [25][26][27] ceramics, [28][29][30] …”
Section: Difficulties Involved In Assessing the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…29 -34 The administration of factor XIII has shown to accelerate fracture healing and increase bone stability in various different osteotomy experiments, 35,36 to promote the osseointegration/stability of implants and the healing of pseudoarthroses, 37 as well as to accelerate the incorporation and remodelling of bone grafts. 38,39 In a fibrin-alginate bead system previously evaluated for the cultivation of periosteal cells, 40 periosteal cells were cultivated after initial monolayer culture under osteogenic culture conditions and the influence of three different growth factors that support osteogenic differentiation. The fibrin beads are effective carrier structures that support the bone-and cartilage-forming potential of different types of cells that can be combined with different matrices for special requirements of cell culture.…”
Section: Introductionmentioning
confidence: 99%
“…We had long been using fibrin glue in lateral suboccipital craniectomy to prevent cerebrospinal fluid leakage from the mastoid air cells. An unexpected observation on CT scan, that bone fragments applied with the fibrin glue on the dural surface regrew a bone plate several months later, drew our attention to the possibility that allogenic fibrin glue could have an osteopromotive effect, even though such effects have not been seen using xenogeneic fibrin glue in animals [7,8,14,32]. This observation prompted the present study to test regeneration of bone following regrafting of bone fragments with allogenic fibrin glue in patients.…”
Section: Introductionmentioning
confidence: 94%